QSAR Studies of Some Pharmacological Schiff Base Compounds - Arora, Kishor (Asian Journal of Chemistry, 2010)
A set of nine Schiff base compounds containing antiinflammatory activity were subjected to quantitative structural and activity relationship (QSAR) studies using various combinations of electronic, spatial and structural descriptors. Experimental data of these compounds are available which prompted study of their theoretical parameters using AM1 semi-empirical quantum-chemical studies and to correlate these properties with their activities according to QSAR studies. Statistical significance of the proposed models have been discussed. Among the various descriptors for the proposed models, some of the descriptors viz., energy of highest occupied molecular orbital, energy of lowest unoccupied molecular orbital, bend energy, dipole moment and principal moment of inertia Y-component gave good statistical significance.